EVALUATION OF TWO CHEST TOMOSYNTHESIS CYSTIC FIBROSIS SCORING SYSTEMS USING HIGH-RESOLUTION COMPUTED TOMOGRAPHY BRODY SCORING AS REFERENCE. Issue 3 (5th May 2021) - Rossi Norrlund, Rauni; Meltzer, Carin; Söderman, Christina; Johnsson, Åse Allansdotter; Vikgren, Jenny; Molnar, David; Gilljam, Marita; Båth, Magnus
Abstract: Purpose: To evaluate two chest tomosynthesis (CTS) scoring systems for cystic fibrosis (CF), one system developed by Vult von Steyern et al . (VvS) and one system based on the Brody scoring system for high-resolution computed tomography (HRCT) (modified Brody (mB)). Brody scoring of HRCT was used as reference. Methods: In conjunction with routine control HRCT at clinical follow-up, 10 consecutive adult CF patients underwent CTS for research purposes. Four radiologists scored the CTS examinations using the mB and VvS scoring systems. All scores were compared to the Brody HRCT scores. The agreement between the evaluated CTS scoring systems and the reference HRCT scoring system was determined using Spearman's rank correlation coefficient and the intraclass correlation coefficient (ICC). Major findings: Spearman's rank correlation coefficient showed strong correlations between HRCT score and both the mB and the VvS CTS total scores (median rs  = 0.81 and 0.85, respectively). The ICC showed strong correlation between the CTS scoring systems and the reference: 0.88 for mB and 0.85 for VvS scoring. The median time for scoring was 20 and 10 minutes for the mB and VvS scoring systems, respectively. Conclusions: Both evaluated CTS scoring systems correlate well with the reference standard Brody HRCT scoring. The VvS CTS scoring system has a shorter reading time, suggesting its advantage in clinical practice.